Development of Environment-Based Contextual Learning Model for improving the English Language Competency of Children with Disabilities in Inclusive Schools - Roni La'biran; Markus Deli Gerik Allo; Resnita Dewi; Judith Raty Tandi Arrang; Hilda Kalvin; Kevin Imanuel (Eduvelop: Journal of English Education and Development, 2026)
This study aims to develop an environment-based contextual learning model designed to enhance the English language competency of children with disabilities in inclusive schools. The research adopts a research and development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The model emphasizes the use of real-life environmental contexts as learning resources, integrating natural surroundings, school environments, and community-based materials to create meaningful learning experiences. Data were collected through observation, interviews, and performance assessments involving English teachers, students with disabilities, and inclusive education experts. The results indicate that the environment-based contextual learning model effectively increases students’ motivation, participation, and English proficiency, particularly in vocabulary mastery and communicative competence. The model also promotes inclusive interaction and supports differentiated learning strategies tailored to students’ needs and abilities. Overall, this study concludes that environment-based contextual learning provides a practical and inclusive pedagogical framework for improving English language competency among children with disabilities in inclusive educational settings.